Health Education Triase terhadap Tingkat Kecemasan Keluarga Pasien pada Kategori Triase P2 dan P3 - Renny Triwijayanti; Annisa Rahmania (Jurnal Keperawatan Silampari, 2023)
This study aims to analyze the effectiveness of triage health education on the anxiety level of the families of patients with priority triage P2 and P3 in the hospital's emergency room. The research method used in this study is quantitative with a pre and post-test design. The results of the study found that 95% believed the age of the respondents with an interval between 33.49 to 40.58, the patient's families were female (61.3%) more than male (38.7%), and the highest education was high school (SMA). 67.7%) and a significant difference in anxiety before and after the intervention with a p-value <0.05. In conclusion, there is a substantial difference in pressure between before and after the intervention, so health education triage is effective on anxiety levels. Keywords: Patient's Family Anxiety, Health Education, Triage